2002
DOI: 10.1021/ie020088k
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nonisobaric and Isobaric Steps on O2 Pressure Swing Adsorption for an Aerator

Abstract: The effects of nonisobaric and isobaric steps on a two-bed O 2 pressure swing adsorption (PSA) packed with zeolite 5A were investigated. In addition, the operating conditions in the O 2 PSA were studied to supply the various O 2 concentrations to the oxygen aerator efficiently. Because the velocity variation along the bed and the related Mass Transfer Zone (MTZ) shape at the isobaric and nonisobaric steps were affected by the diffusion rate, the concentration-dependent rate parameter in a modified linear drivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 21 publications
(49 reference statements)
0
14
0
Order By: Relevance
“…The pressure history during a PSA experiment at the feed or bed end was fitted by polynomials and used as a boundary condition for the overall mass balance 21…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The pressure history during a PSA experiment at the feed or bed end was fitted by polynomials and used as a boundary condition for the overall mass balance 21…”
Section: Mathematical Modelmentioning
confidence: 99%
“…An experimental and simulation study of a PSA unit which is running a traditional Skarstrom cycle and a Skarstrom cycle with co-current equalization owing to separate oxygen from air using a 5A zeolite has been proposed by Mendes et al [11] in 2001. Moreover, a small-scale two-bed six-step PSA process using zeolite 13X was performed by Jee et al [27][28][29][30] in order to provide oxygen-enriched air. They showed that there is a strong effect of feed flow rate on O2 purity.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of temperature variations in gas phase during adsorption as a function of time is illustrated in Figure 2(c). It is obviously seen that there is a relatively high accuracy in the simulation of experimental data [27] .…”
Section: Resultsmentioning
confidence: 99%
“…The assumption of neglecting radial gradient was widely accepted by numerous adsorption studies like Rota and Wankat [9], Jee et al [10], and Kim et al [11].…”
Section: Mathematical Modelingmentioning
confidence: 99%